[Correspondence] - Gribbell, Lise (Adam Matthew Digital, 1866)
Letters written by Lise Gribbell of Victoria, B.C. regarding two Tsimshian women, Isabella Keith and Margaret, who were sent to join the Metlakahtla settlement established by William Duncan; also, letters from Isabella and Margaret to Mrs. Gribbell